Assessing the potential role of microorganisms in the production of seedlings for the restoration of Albany Thicket - Mpama, Nelisa (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The role of microorganisms in restoration of the Albany Thicket has not been well documented, although the benefits to plants of these various interactions has been well documented. Microorganisms are chief ecological engineers and assist in resolving environmental problems and act to restore degraded ecosystem function by forming mutual relationships with the roots of the plants. The aim of this study was to assess the potential of microorganisms for the improved biomass production of selected woody and succulent seedlings used in mesic thicket restoration. Three tree species were selected for propagation in this study namely; Mystroxylon aethiopicum Scutia myrtina and Aloe ferox. Soil samples were collected from a degraded and intact thicket site from Bathurst, South Africa. Soils were evaluated for number of arbuscular mycorrhizal (AM) spores, mycorrhizal infectivity potential and nutrient availability both before and after seedling propagation. Pasteurized soil from the degraded site was used in a pot trial. Ten replicates seedling for plant species were planted and subjected to four treatments which included inoculation with AM fungi and the rhizobacterium, Enterobacter sp., alone and in combination; the fourth treatment was an un-inouclated control. Plant growth parameters were recorded at regular intervals where appropriate and seedlings were harvested after 24 weeks for biomass measurements and AM colonisation assessments. Although generally low (< 1 spore per gram) the density of AM fungal spores was significantly higher in soils from the intact site when compared with soils from the degraded site. The mycorrhizal potential of the soils was however not significantly different. Mystroxylon aethiopicum seedling shoot height, canopy diameter and shoot biomass showed a significant increase when inoculated with AM fungi while S. myrtina seedlings showed increased shoot height when inoculated with both AM fungi and Enterobacter sp. Aloe ferox seedlings did not respond to microbial inoculation. The concentration of soil P and Na increased in treatments with Enterobacter sp. alone and in combination with AM fungi. Mystroxylon aethiopicum and S. myrtina seedlings showed a dependency on microbial inoculants indicating the importance of inoculation in the nursery before planting out into the field. Overall AM fungal inoculants applied to seedlings can be used to compensate for nutrient deficiency in soils. Although the Enterobacter isolate used was known to have various plant growth promoting capabilities. It is recommended that other rhizobacterial isolates be investigated.
Keywords: Vesicular-arbuscular mycorrhizas; Rhizobacteria; Restoration ecology -- South Africa -- Albany; Microorganisms